Seasonal variations of Diptera assemblages in urban green patches of Cordoba city, Argentina: Same richness, different composition - Montes, Marcela (2020)
Seasonality can have a direct influence on thestructuring of insect communities due to different preferences or tolerances tothe climatic conditions of the species that compose them. The aimof this study was to evaluate seasonal changes in adult Diptera assemblages ofurban green patches in a southern temperate region. Dipterans were sampled fromvegetation with a G-VAC (aspirator) in urban green patches in Córdoba city,Argentina, during the summer and winter of 2014. Overall, dipterans were moreabundant in summer than in winter but globally, their richness was similar. However,richness per site was significantly lower in the winter, reflecting a heterogeneous distribution and higher family turnover during this season. Family composition and/ortheir relative abundances differed between seasons, reflecting the seasonal segregationof several Diptera families in this temperate region of the southern hemisphere.